Pemanfaatan Sosial Media Di SMKN 12 Kab. Tangerang - Adinda Nurkhalifah Akbal; Ardiansyah; Dimas Aditya Candra; Muhammad Sheva Nurmansyah; Nur Sa’adah Lubis; Panji Sofyan Zakaria; Rahmat Julianto (CV. Multi Kreasi Media, 2023)
-In carrying out daily activities, humans today certainly cannot escape the use of social media. Technological advances, especially in communication and entertainment media, have a two-way impact, namely positive and negative, user policies in social media are very influential. Currently online social media such as Facebook, Instagram, YouTube, Twitter, and others have even changed lifestyles. With the easy dissemination of information, it is expected that students as users of social media can filter the information they get. With the socialization of the benefits of social media which was attended by Vocational High School students, it is hoped that it will add to the participants' understanding of what must be utilized in the all-digital era and cannot be separated from social media and in this activity we invite students to use social media for activities positive such as the exchange of information, especially in the scope of the school.